Investigating the Impact of Social Capital on Elderly Quality of Life in Surakarta: A Multilevel Analysis - Mentary Febryant Putry; Argyo Demartoto; Bhisma Murti (Journal of Epidemiology and Public Health, 2025)
Background: A good quality of life is the goal of every individual in life. This quality of life indicates that a person is healthy and prosperous, so that they can live a normal life in the community, especially for the elderly population. This study aims to analyze the variables of the influence of social capital on the quality of life of the elderly at the individual level and the posyandu level.Subjects and Method: This study is a study using a cross-sectional design conducted in 25 elderly posyandu in Surakarta from August to September 2024. The sample consisted of 200 elderly people who were selected by probability sampling. The independent variable in this study is social capital. The dependent variable is quality of life. Data collection was carried out by questionnaire. The analysis data uses multilevel analysis.Results: The results of the multilevel analysis that has been carried out in this study stated that the social capital and quality of life of the elderly (b=1.29; CI 95%= 1.12 to 1.47; p<0.001), directly influenced by age (b=0-1.16; CI 95%= -3.64 to 1.31; p= 0.035), gender (b=8.91; CI 95%= 7.21 to 10.62; p<0.001), education (b=10.27; CI 95% = 8.73 to 11.81; p<0.001).Conclusion: Social capital has a statistically significant positive influence on the quality of life of the elderly.